ANALISIS STRATEGI BELAJAR MANDIRI SISWA KELAS VI DALAM MENGHADAPI UJIAN DI SEKOLAH DASAR - Muslim, Aji Heru; Wakhid, Imanulloh (Jurnal Kiprah, 2018)
School exanimation is a determining moment for the students. Some strategies are needed in order to achieve maximal results because they can help the students to understand and implement their knowledge and determine their success in examination. This research aimed to find out the self-studying strategy on the sixth graders of SD Negeri 1 Kedungwuluh Kidul in facing examination using mixed method. The populations of this research were 28 sixth graders for the quantitative method of this research and 10 of them were chosen for the qualitative method using purposive sampling. Questionnaire was used to collect quantitative data while interview and document were used to collect qualitative data. The quantitative data were then analyzed using percentage while the qualitative data were analyzed using Miles and Huberman model. The results of quantitative data analysis showed that self-studying of the sixth graders in facing examination at SD Negeri 1 Kedungwuluh Kidul mostly used some strategies such as: 1) asking strategy which belonged to elaboration learning with the percentage of 60.7%; 2) highlighting which one belonged to the reviewing strategy with the percentage of 57.1%; and reviewing which one belonged to reviewing strategy with the percentage of 53.5%.